Implementierung des eLearning-Projekts NESTOR - Back, David A.; Schmidmaier, Gerhard (Der Chirurg, 2012)
Background: Modern internet-based information technologies offer great possibilities to create and improve teaching methods for students. The eLearning tool NESTOR (Network for Students in Traumatology and Orthopedics) presented here was designed to complement the existing clinical teaching in orthopedics and traumatology at the Charité, University Medicine Berlin. Materials and methods: Using a learning management system, videos, podcasts, X-ray diagnosis, virtual patients, tests and further tools for learning and study information were combined. After implementation the eLearning project was evaluated by students. Results: The NESTOR project offers various possibilities for knowledge acquisition. Students using the program voluntarily showed a high acceptance whereby 82.4% were very satisfied with the contents offered and 95.3% supported the idea of a future use of NESTOR in teaching. The blended learning approach was positively evaluated by 93.5% of the students. The project received the eLearning seal of quality of the Charité University Medicine Berlin. Conclusion: Using complex eLearning tools, such as the NESTOR project represents a contemporary teaching approach in the teaching of traumatology and orthopedics and should be offered in a blended learning context as they are well accepted by students.
Gesehen am 31.07.2018
Online publiziert: 12. Mai 2011